PENGARUH HAMBATAN KERJA DAN SUMBER DAYA PEKERJAAN TERHADAP KINERJA KESELAMATAN PADA PEKERJA LAPANGAN PT. PERUSAHAAN LISTRIK NEGARA (PERSERO) BANDA ACEH - Aja Durrijal; Ade Irma Suryani (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
Abstract: This study aims to measure the effect of Job Barriers and Employment Resources onSafety Performance in PT. Perusahaan Listrik Negara (Persero) Banda Aceh. The sample used inthis study is the field workers of PT. Perusahaan Listrik Negara (Persero) Banda Aceh, amountingto 48 respondents. Data collection equipment used in this study is a questionnaire. The samplingtechnique used is saturated sampling. Multiple linear regression is used as an analytical method todetermine the effect of all the variables involved. The results showed that partially the Excess Roleand Job Resources variables had a positive and significant effect on the Safety Performancevariable. But the variable Job Insecurity shows a negative and significant effect on the SafetyPerformance variable.